2015
DOI: 10.1002/chp.21293
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Test-Enhanced Learning in Continuing Health Sciences Education: A Randomized Controlled Trial

Abstract: The null findings in the present study are inconsistent with previous research showing the pedagogical benefits of testing relative to studying. Given that most TEL research focuses on novice learners, who lack strong associative memory networks, it is possible that TEL is specific to novices and not generalizable to experts. Alternative explanations focus on the importance of repeated, distributed testing with feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…In contrast to our findings, no such between-subject difference was found in a study where only a single test was given for learning activity of practicing physicians. 20 In comparison, our study used four tests as learning exercise in lectures. Previous studies have established the relation between number of tests taken and improvement in long-term retention of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, no such between-subject difference was found in a study where only a single test was given for learning activity of practicing physicians. 20 In comparison, our study used four tests as learning exercise in lectures. Previous studies have established the relation between number of tests taken and improvement in long-term retention of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Other strength of the study was absence of any attrition that has affected the measure of TEL effectiveness in previous studies. 13 , 16 , 20 - 22 …”
Section: Discussionmentioning
confidence: 99%
“…For example, McConnell et al found that physicians who completed a short answer test following a large group passive CME activity did not remember any more information on a test four weeks later than physicians who studied the same information. 12 In contrast, Larsen et al 13 found that within a CME context, physicians who received weekly short-answer quizzes performed better on a final test five and a half months later, relative to those who repeatedly studied the same information.…”
Section: Introductionmentioning
confidence: 94%
“…One major difference between these two studies is the number of intervening tests provided to CME participants; Larsen et al 13 provided participants with four intervening quiz/study activities prior to the final test, while McConnell et al 12 only provided a single quiz/study activity. Research shows that increasing the number of intervening tests enhances TEL, provided the tests are separated by a long enough period (e.g., days, weeks) to require effortful memory retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, negative studies of retrieval practice have been published as well. 38,39 Principles have emerged from the psychology and education literature that can guide implementation of retrieval practice to increase the likelihood that long-term retention is achieved. Four of these are considered below: test format, repetition, spacing, and feedback (►Fig.…”
Section: How Is Retrieval Practice Best Implemented?mentioning
confidence: 99%